The pathogenic mechanism of monosodium urate crystal-induced kidney injury in a rat model - Li, Delun; Li, Yimeng; Chen, Xuesheng; Ouyang, Jianting; Lin, Danyao; Wu, Qiaoru; Fu, Xinwen; Quan, Haohao; Wang, Xiaowan; Wu, Shouhai; Yuan, Siyu; Liu, Anqi; et al. (Frontiers in Endocrinology, 2024)
Gouty nephropathy (GN) is caused by the precipitation of monosodium urate (MSU) crystals usually in the kidney tubules especially collecting ducts in the medulla.Previous animal models have not fully reproduced the impact of MSU on kidneys under non-hyperuricemic conditions. The results of this study suggest that intrarenal injection of MSU crystals may result in urate nephropathy. In the group treated with MSU, the upper pole of the rat kidney was injected intrarenally with 50 mg/kg of MSU, while the lower pole was injected with an equivalent volume of PBS solution.The body weight and kidney mass of the rats were observed and counted.H&E staining was used to observe the pathological damage of the kidney and to count the number of inflammatory cells.Masoon staining was used to observe the interstitial fibrosis in the kidneys of the rat model. Flow cytometric analysis was used for counting inflammatory cells in rats. ElISA was used to measure the concentration of serum and urine uric acid, creatinine and urea nitrogen in rats. At the MSU injection site , a significantly higher infiltration of inflammatory cells and a substantial increase in the area of interstitial fibrosis compared to the control group and the site of PBS injection were observed. The serum creatinine level was significantly increased in the MSU group. However, there were no significant differences in the rats' general conditions or blood inflammatory cell counts when compared to the control group. This indicates that the method of intrarenal injection did not induce surgical infection or systemic inflammatory response. The injection of urate crystals into the kidney compromised renal function, caused local pathological damage, and increased inflammatory cell infiltration and interstitial fibrosis.This study presents a new method for modelling urate nephropathy induced by MSU crystals in rats, contributing to a better understanding of this clinical condition and its underlying molecular mechanisms.